2012
DOI: 10.3390/v4123804
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Cowpea Mild Mottle Carlavirus on Yardlong Bean (Vigna unguiculata subsp. sesquipedalis) in Venezuela

Abstract: Yardlong bean (Vigna unguiculata subsp. sesquipedalis) plants with virus-like systemic mottling and leaf distortion were observed in both experimental and commercial fields in Aragua State, Venezuela. Symptomatic leaves were shown to contain carlavirus-like particles. RT-PCR analysis with carlavirus-specific primers was positive in all tested samples. Nucleotide sequences of the obtained amplicons showed 84%–74% similarity to corresponding sequences of Cowpea mild mottle virus (CPMMV) isolates deposited in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 13 publications
0
20
0
2
Order By: Relevance
“…The aphid vectors take a very short time to transmit these viruses to plants such that application of insecticides is not effective. The same is true for the nonpersistently whitefly transmitted CPMMV (Brito et al, 2012), which has been detected in common bean in Tanzania (Mink and Keswani, 1987;Vetten and Allen, 1991). Conversely, pesticide use may prevent or reduce infection by persistently transmitted viruses.…”
Section: Control Of Vectorsmentioning
confidence: 70%
“…The aphid vectors take a very short time to transmit these viruses to plants such that application of insecticides is not effective. The same is true for the nonpersistently whitefly transmitted CPMMV (Brito et al, 2012), which has been detected in common bean in Tanzania (Mink and Keswani, 1987;Vetten and Allen, 1991). Conversely, pesticide use may prevent or reduce infection by persistently transmitted viruses.…”
Section: Control Of Vectorsmentioning
confidence: 70%
“…These particles form aggregates in the form of sheets or bundles and often brush-like inclusions (Brunt et al, 1983;Almeida et al, 2003Almeida et al, , 2005. CPMMV is transmitted in a nonpersistent manner by the whitefly Bemisia tabaci (Munyappa & Reddy, 1983;Jeyanandarajah & Brunt, 1993;Naidu et al, 1998;Almeida et al, 2005;Marubayashi et al, 2010;Brito et al, 2012). Seed transmission appears to be dependent on the viral isolate: for a Ghana isolate of CPMMV, seed transmission occurred in soybean, cowpea and with lower frequency in common bean (Brunt & Kenten, 1973); in Venezuela it was demonstrated that CPMMV can be transmitted by yardlong bean seeds (Brito et al, 2012), but Almeida et al (2005) reported that a Brazilian CPMMV isolate was not transmitted by soybean seeds.…”
Section: Introductionmentioning
confidence: 99%
“…The seed-borne virus transmission can also be an important component of the epidemiology of the disease in the field. It has already been reported that different isolates of CPMMV can be seed transmitted, as observed for cowpea, soybean and common bean seeds in Ghana (Brunt & Kenten, 1973) and yardlong bean seeds in Venezuela (Brito et al, 2012). In Thailand, the virus was observed to be transmitted by soybean seeds at a frequency lower than 1% (Iwaki et al, 1982) but in India, the seed-borne nature of the virus was detected in several soybean cultivars with higher rates of transmission, ranging from 0.62% to 14.2% (Yadav et al, 2013).…”
Section: Discussionmentioning
confidence: 91%